Strategi Pemberdayaan Untuk Meningkatkan Pendapatan Petani Rumput Laut - S. Kaseng, Ernawati (Research Agency for Humanity and Urban, 2023)
Poverty caused by income inequality and social inequality that occurs in coastal communities is the main problem that has been of concern to the Government so far, so an empowerment strategy is needed to alleviate it. For this reason, the purpose of the article is to describe empowerment strategies to increase the income of seaweed farmers. The review method uses a literature study method where the data obtained are compiled, analyzed, then make conclusions. Type of data, namely secondary data. Data collection techniques, through the stages of taking data from the library, reading, recording, then processing data. The results of the study show that stakholder's efforts to carry out empowerment aim to increase community independence. Through empowerment approaches and strategies, climate is created, power strengthening, and protection of communities as subjects of development. The coastal community empowerment strategy carried out by the South Sulawesi Provincial Government is based on the principle of sustainability, the principle of consistency, the principle of integration, the principle of legal certainty, the principle of partnership, the principle of equity, the principle of participation, the principle of openness, the principle of accountability, and the principle of justice. Empowerment as non-formal education, the implementation of the seaweed farmer empowerment program is carried out through a learning process to improve knowledge and skills of group strengthening, dissemination of seaweed cultivation technology, and implementation of training and counseling to seaweed farmers at the farmer group level on an ongoing basis.